The Effect of Insulin Treatment on Rac1 Expression in Diabetic Kidney. (April 2013) - Gumustekin, Mukaddes; Micili, Serap Cilaker; Arici, Mualla Aylin; Karaman, Meral; Guneli, Mehmet Ensari; Tekmen, Işil
<x xml:space="preserve">Abstract</x> This study was designed to evaluate the renoprotective effect of insulin on diabetic nephropathy through Rac1 inhibition. Twenty Wistar rats were divided into three groups: control (C), diabetic (D), and insulin-treated diabetic (D + I). Diabetes was induced by a single streptozotocin (STZ) injection (45 mg/kg i.p.) in adult male rats. Diabetic animals were treated subcutaneously with insulin (6 U/kg), or saline once a day for 8 weeks. Age-matched control rats received only saline. The kidney tissue samples were analyzed by immunohistochemical staining for Rac1 and cleaved caspase-3 expressions and using the TUNEL method for determining apoptotic cells. Diabetes increased the number of TUNEL (+) cells and cleaved caspase-3 and Rac1 expression levels in kidney. Administration of insulin for 8 weeks reduced Rac1 expression and ameliorated histopathological changes in kidney of STZ-induced diabetes model. These results may suggest that the renoprotective effect of insulin at least partly results from inhibition of Rac1 overexpression.